2017
DOI: 10.2147/dddt.s143805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of echinacoside on kidney fibrosis by inhibition of TGF-β1/Smads signaling pathway in the db/db mice model of diabetic nephropathy

Abstract: Kidney fibrosis and renal tubular epithelial-to-mesenchymal transition (EMT) are the main pathological changes of diabetic nephropathy (DN), which eventually leads to end-stage renal disease. Previous studies have suggested that echinacoside (ECH) is antifibrotic in the liver. However, the effect of ECH on kidney fibrosis in DN and its mechanisms are unknown. This study was performed to explore the effect of ECH on kidney fibrosis and also the molecular mechanisms of ECH in a db/db mice model of DN. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 30 publications
5
45
0
1
Order By: Relevance
“…ROS is associated with EMT induced by TGF-β1, aldosterone, albumin or oxidized low-density lipoprotein, which is consistent with earlier studies (39). The upregulation of TGF-β1 in vitro and in vivo serves a significant role in the pathogenesis of DN (15,40) and it was demonstrated that TGF-β1 expression was increased under HG conditions. H 2 O 2 , which was used as an agent to simulate oxidative stress, also increased the expression of TGF-β1.…”
Section: Gsh (Mg/g Protein) T-sod (U/mg Protein) Mda (µMol/g Protein)supporting
confidence: 88%
“…ROS is associated with EMT induced by TGF-β1, aldosterone, albumin or oxidized low-density lipoprotein, which is consistent with earlier studies (39). The upregulation of TGF-β1 in vitro and in vivo serves a significant role in the pathogenesis of DN (15,40) and it was demonstrated that TGF-β1 expression was increased under HG conditions. H 2 O 2 , which was used as an agent to simulate oxidative stress, also increased the expression of TGF-β1.…”
Section: Gsh (Mg/g Protein) T-sod (U/mg Protein) Mda (µMol/g Protein)supporting
confidence: 88%
“…), as well as renal tubular basement membrane thickening and tubular atrophy (Tang et al . ), respectively. We showed elevated UTX in all three major renal cell types involved in DKD, implicating a critical role of UTX in DKD.…”
Section: Discussionmentioning
confidence: 95%
“…1). Mesangial cells, podocytes and tubular cells are all involved in the development of DKD, which are responsible for mesangial expansion and accumulation of extracellular matrix (Gruden et al 2005), podocyte loss, podocyte foot processes fusion and effacement (Maezawa et al 2015), as well as renal tubular basement membrane thickening and tubular atrophy (Tang et al 2017), respectively. We showed elevated UTX in all three major renal cell types involved in DKD, implicating a critical role of UTX in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…Huiling Wu et al reported that TLR4/NF-κB signaling pathway was activated in DN model in vivo [33]. Fengjuan Tang et al demonstrated that echinacoside was able to inhibit kidney brosis through regulating TGF-β1/Smad signaling pathway [34]. Additionally, Yaning Wang et al reported that astragaloside delayed the process of renal brosis in diabetic mice by in uencing the TGF-β/SMADS signaling pathway and downregulating TGF-β1, SMAD2/3 [35].…”
Section: Discussionmentioning
confidence: 99%